EVALUASI DAN REKOMENDASI UNIT INSTALASI PENGOLAHAN AIR LINDI DI TPA TEGALASRI KABUPATEN BLITAR - Bima Okvanda Pratama; M Abdus Salam Jawwad (Yayasan Nusantara Hasana Berdikari, 2023)
Until now, the management and management of garbage and waste that is not good is a serious problem faced by almost all cities and regions in Indonesia. The problem of waste management in Indonesia is not just due to technological and economic limitations, but rather because of the disproportionate culture, old habits, behavior and ways of thinking of the people, so things like this must be changed. As the population of Blitar Regency increases, the volume of waste generated will also increase, so that it can reduce the need for landfill land. Currently, waste management is still very dependent on the existence of landfills. In fact, the existence of landfills often causes social conflict and environmental pollution, such as leachate pollution, especially landfills that are not operationally standardized. The purpose of this study is to provide recommendations for the management of leachate waste water in TPA Research which is used using descriptive analysis methods with a quantitative approach. Based on the results of research that has been carried out regarding the evaluation of the Tegalasri landfill leachate treatment installation unit, this has not been going well. in this research.